PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN LAHAN GAMBUT DI DESA SUNGAI KAYU ARA KECAMATAN SUNGAI APIT KABUPATEN SIAK - Azirman "; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sungai Kayu Ara Village is an area that is prone to land and forest cover because most of the area is peatland. To prevent land and forest fires, the community's role is needed. One form of fire prevention is the empowerment of the community. community empowerment is carried out namely onion cultivation in peatlands. The choice of onions as a cultivation commodity because it has high prospects and a short harvest time is around 50-60 days. The purpose of this study is to look at community empowerment in the management of peatlands in Sungai Kayu Ara Village and to find out supporting and inhibiting factors in community empowerment. This type of research is a qualitative research with a descriptive approach. Collection of data needed both primary and secondary data is collected through interviews, observations, and documentation then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that community empowerment in Sungai Kayu Ara Village was not optimal. This non-optimal empowerment is due to decreased community participation and crop failures in the second and third plantations. The factors that support this empowerment are the involvement of NGOs and other supporting facilities besides the factors that inhibit this empowerment so that it is not yet optimal, namely the traditional mindset of the community and poor financial management.                                                                                                        Keywords: Peatlands, Community Empowerment, Onion Cultivation